STUDENTS’ PERCEPTION OF SOCIAL MEDIA TO LEARN ENGLISH - Harun, Fitri G.; Pelenkahu, Noldy; Olii, Sanerita T. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
This study aims to determine students' perceptions of social media to learn English. It was conducted at the Department of English Education, Faculty of Languages ​​and Arts, Universitas Negeri Manado. The method used in this study is qualitative method. The instrument for data collection was a questionnaire distributed 25 respondents of eight-semester students of the 2018 academic year. Students' reactions to each item in the spread questionnaire were examined and conferred by the researcher's understanding, opinion, experience, and outcome from hearing a song. As examples of all students, several questions were accepted positive. Based on the results, more than half of the students agree that YouTube song videos help them to improve their pronunciation skills because apart from being able to practice pronunciation, they also enhance their vocabulary. So, the results of this study indicate that learn through YouTube by using English songs video is more helps them to learn English. The research showed that YouTube songs video are a good learning source in learning English.